MEDICAL TOURISM IN GEORGIA: CURRENT BURRIERS AND RECOMMENDATIONS - Tengiz Verulava; Revaz Jorbenadze (Malaysian Journal of Public Health Medicine, 2018)
The aim of this study is to determine the effective factors that influence the development of medical tourism in Georgia. Qualitative and quantitative methods were used for research. Within the qualitative research the experts of medical tourism were interviewed. Within the qualitative research this study investigates medical tourists’ expectations and perceptions regarding healthcare services. Study tools were prepared on the basis of specially developed “Medical Outcomes Study, Patient Satisfaction Questionnaire” (MOS PSQ-III). The results reveal that policies and regulations, government support, costs, capacity problems, and the healthcare needs of the local community are the main barriers to the development of such tourism. Several strategies for lifting these barriers are suggested, such as new promotional activity policies, government action to encourage investment in the medical tourism market, and cooperative efforts by the hospitality sector and medical institutions to develop medical tourism products. This paper sheds light on a poorly researched field in the Georgian context. It provides directions for hospital managers to develop strategies which will meet patients’ expectations of service quality and increase their competitiveness in the health tourism market.